Well-posed reduction formulas for the q-Kampé-de-Fériet function - Chu, W.; Zhang, W. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
By using the limiting case of Watson’s q-Whipple transformation as n → ∞, we investigate the transformations of the nonterminating q-Kampé-de-Fériet series. Further, new formulas for the transformations and well-posed reduction formulas are established for the basic Clausen hypergeometric series. Several remarkable formulas are also found for new function classes beyond the q-Kampé-de-Fériet function.